A sociology of spirituality - Flanagan, Kieran; Jupp, Peter C. (Theology and religion in interdisciplinary perspective series, 2007)
Introduction / Kieran Flanagan -- Spirituality : some disciplinary perspectives / Peter R. Holmes -- The spiritual revolution : another false dawn for the sacred / David Voas and Steve Bruce -- The holistic milieu and spirituality : reflections on on Voas and Bruce / Paul Heelas -- Beyond secularisation versus sacralisation : lessons from a study of the Dutch case / André Droogers -- Spirituality on the margin of the church : Christian spiritual centres in the Netherlands / Peter Versteeg -- Why so many women in holistic spirituality? : a puzzle revisited / Linda Woodhead -- Contentious headscarves : spirituality and the state in the twenty-first century / Paul Chambers -- Georg Simmel : religion and spirituality / Ivan Varga -- Spirituality : from a religious concept to a sociological theory / Giuseppe Giordan -- In search of spiritual capital : the spiritual as a cultural resource / Mathew Guest -- The embodied spirituality of the post-boomer generations / Richard W. Flory and Donald E. Miller -- Visual spirituality : an eye for religion / Kieran Flanagan -- Conclusion / Kieran Flanagan and Peter C. Jupp